Implikasi Ontologi Filsafat Pendidikan Islam terhadap Pemahaman Hakikat Manusia dalam Kurikulum MI Muhammadiyah Sonorejo Sukoharjo - Wauran, Meissara Putri Andannari; Mujiburrohman, Mujiburrohman (Lembaga Yasin AlSys, 2025)
This study originates from the importance of ontological understanding in the philosophy of Islamic education as a foundation for shaping conceptions of human nature in primary education. The research aims to explore the ontological values underpinning the curriculum of MI Muhammadiyah Sonorejo Sukoharjo and how these values influence character formation and the development of students’ potential. A descriptive qualitative method was employed, using a field study approach through interviews, observations, and documentation, which were analyzed thematically. The findings indicate that the understanding of humans as spiritual, social, and potential-bearing beings is reflected in the curriculum structure, learning strategies, and character-building approaches. The institution's curriculum is grounded in an ontological foundation that views humans as insan kamil, with an integral educational mission. These findings underscore the significance of developing Islamic primary education curricula rooted in Islamic philosophy to shape holistic individuals both spiritually and socially.